The changing portrayal of women in the novels Shirley, The Mill on the Floss and Sons and Lovers - Yasmin, Fahmida (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2014.